A novel torque vectoring system for enhancing vehicle stability. (17th May 2019) - Sun, Tao; Gong, Xuwei; Li, Bin; Wu, Jian
Aiming for improving the handling and stability performance of all-wheel-drive (AWD) vehicles, a novel torque vectoring system (TV) is proposed in this paper by distributing engine torque to the front and rear axles as well as transmitting the torque between the two rear wheels. Unlike brake-based control system such as electronic stability control (ESC), the TV system can extend the cornering stability limit without interference with the vehicle longitudinal dynamics, thus improve the vehicle stability while making the handling feel smooth and consistent. Torque vectoring control strategy is developed to allocate torque to each wheel under different driving conditions. LQR controller is designed to generate the corrective yaw moment. Simulations were firstly conducted to validate the effectiveness of this system. And then a scaled vehicle is built based on dynamic similarity of the Buckingham Pi theorem to further verify the proposed TV system. Compared with a conventional AWD vehicle with open differentials, the vehicle with the proposed TV system shows better understeer characteristics and increases the maximum level of lateral acceleration.